Factores que limitan la formalización del comercio ambulatorio en la ciudad de Chepén. - Quiroz Briones, José Luis (2011)
This Thesis, it proposes to determine the factors that limit the formalization of street vending in the City of Chepén and how to determine in their operation and Development. Knowledge of these factors will propose solutions to informal traders can develop business and access to the benefits offered by the formalization. The analytical method is used. The main results are 89.86% of drivers who do business in street vending Ezequiel Gonzales Cáceda Avenue is considered a street vendor, the 53.62% of traders are 5 years or more of exercise, 40.58% requested a bank loan at times, the 85.71% of the hawkers who have applied for a bank loan if you were treated, 66.67% have not thought formalize their business, 43.48% formalize your business by accessing bank loans is 32.60% the street because it lacks an entrepreneurial culture, the 21.74% is the high cost of the main conclusions are formalized 66.67% have not thought formalize their business, 46.38% of the hawkers are more than 5 years of practice, the factors that limit the role of street vending in the city of Chepén are the lack of an entrepreneurial culture and the high costs of formalization.